2021
DOI: 10.1021/acs.jced.1c00684
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvents Composed of Urea and New Salts of a Choline Family for Efficient Ammonia Absorption

Abstract: Two new deep eutectic solvents (DESs) composed of urea (U) and salts of a choline family such as dimethyl-di(2hydroxyethyl)-ammonium chloride [Me 2 C OH 2 N]Cl and methyl-tri(2hydroxyethyl)-ammonium chloride [MeC OH3 N]Cl mixed in a 1:1 molar ratio were prepared. Their densities, viscosities, refractive indices, and properties related to the ammonia absorption were thoroughly investigated. We found that the obtained DESs show an absorption capacity of 2.078 and 2.632 mol NH3, respectively, at 313.2 K and 101.3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 74 publications
0
10
0
Order By: Relevance
“…Therefore, the effect of water on NH 3 solubilities in metal‐based DESs prepared in this work is very minor. Table 2 presents the comparison of NH 3 solubilities in different DESs and ILs 25,36–50,65–76 . It is found that the solubilities of NH 3 in metal‐based DESs prepared in this work are remarkably high, especially at low pressures.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations
“…Therefore, the effect of water on NH 3 solubilities in metal‐based DESs prepared in this work is very minor. Table 2 presents the comparison of NH 3 solubilities in different DESs and ILs 25,36–50,65–76 . It is found that the solubilities of NH 3 in metal‐based DESs prepared in this work are remarkably high, especially at low pressures.…”
Section: Resultsmentioning
confidence: 83%
“…Therefore, DESs have the potential to replace ILs for highly efficient and reversible gas absorption 31–35 . As for the application of DESs in reversible NH 3 absorption, there have been some impressive examples such as ChCl + PhOH + EG DESs, 36 NH 4 SCN + Gly DESs, 37 EaCl + Gly DESs, 38 ChCl + TetrZ + EG DESs, 39 MAA + TetrZ DESs, 40 [Im][NO 3 ] + EG DESs, 41 [emim]Cl + BenTriz DESs, 42 [ImH]Cl + Gly DESs, 43 LiCl/EG DESs, 44 and [MeC OH 3 N]Cl/U 45 . After careful examination on these DESs, it can be found that they are typically constituted by one weak acidic compound (e.g., PhOH, NH 4 SCN, EaCl, TetZ, [Im][NO 3 ], BenTriz or [ImH]Cl) that enables acid–base interaction with NH 3 , and one or two hydroxyl compounds (e.g., ChCl, EG, or Gly) that enable hydrogen‐bond interaction with NH 3 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…At present, special attention is given to the deep eutectic solvents (DESs) [ 12 , 13 , 14 ], which seem to be a prospective alternative to recently widely studied room temperature ionic liquids (RTILs) [ 15 , 16 , 17 ], which have proven to be materials with high absorption capacity with regard to ammonia. Deep eutectic solvents possess both similar loading as RTILs and the merits of low cost.…”
Section: Introductionmentioning
confidence: 99%